The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1742-9544.2012.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Clinical Psychology Trainees: Current Research Status and Future Directions

Abstract: The purpose of this article is to present the current status of the literature related to stress in clinical psychology trainees (CPTs), and to offer research directions for investigating stress in this population and ways to enhance self-care in these individuals. The following conclusions emerge from the review: (1) CPTs are vulnerable to elevated stress; (2) undue stress can negatively impact CPTs' personal and professional functioning and, in turn, result in less than optimal standards of care for clients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 95 publications
2
89
1
1
Order By: Relevance
“…Despite CBT being the best validated approach for the treatment of stress [16-19], further clinical research is needed to refine existing protocols and fully exploit its clinical potential. Stress-related disorders cannot be explained simply on the basis of the terrible things that happen to people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite CBT being the best validated approach for the treatment of stress [16-19], further clinical research is needed to refine existing protocols and fully exploit its clinical potential. Stress-related disorders cannot be explained simply on the basis of the terrible things that happen to people.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Cochrane database underlines that “the poor quality of trials, considerable heterogeneity observed between trials and evidence of significant publication bias make the pooled findings insecure.” In other words, even if CBT is the best-validated approach for the treatment of stress [16-19], further clinical research is needed to tune existing protocols and fully exploit its clinical potential.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are noteworthy given that the ACT processes are associated with greater well-being and self-care in health practitioners and that greater mindfulness is associated with better personal and client outcomes in health professionals. 12 Several methodological limitations may explain the lack of statistically significant change in primary outcomes and ACT processes. First, the small sample size limited power to detect statistically significant change; prevention research typically requires large samples …”
Section: Discussionmentioning
confidence: 99%
“…10,11 These ACT training benefits are particularly relevant to psychologists given that they are at risk for burnout and that self-care and psychological flexibility can protect against burnout. 12 ACT training typically involves experiential exercises whereby trainees experience each of the ACT processes and acquire the skills for enhancing these in their own lives, which, in turn, positions them for teaching these processes to clients. 12,13 Owing to ACT being relatively new, few health professionals serving people with MS are trained in it.…”
Section: Act Workhopmentioning
confidence: 99%
See 1 more Smart Citation